Pengaruh Inflasi dan Suku Bunga Terhadap Nilai Tukar Negara-Negara Regional ASEAN - Lutfiansyah, Wisnu Jaya; Nikensari, Sri Indah; Yuniarti, Puji (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The exchange rate is the amount of domestic currency that must be paid to obtain one unit of foreign currency. refers to the most recent changes in the exchange rate. Changes in exchange rates by many things such as inflation and interest rates are related to changes in the exchange rate of a country's currency. This study analyzes the influence of inflation and interest rates on the exchange rates of ASEAN regional countries. Data was taken from the period before and after the peak of the pandemic, namely from 2019-2024 to observe the short- to medium-term impact. The results of the study showed that inflation was found to have a negative relationship with the exchange rate, where an increase in domestic inflation led to currency depreciation. Meanwhile, interest rates show varying influences depending on each country's monetary policy. The study concludes that in the context of economic mapping in ASEAN regional countries over the past 5 years, policies that focus on managing and controlling inflation are more effective in maintaining exchange rate stability than adjusting interest rates.